IMMU-46. EXAMINATION OF THE EFFECTS OF DEXAMETHASONE ON THE EFFICACY OF IMMUNOTHERAPY IN GLIOMA USING GENE-MEDIATED CYTOTOXIC IMMUNOTHERAPY. (11th November 2019) - Koch, Marilin; Zdioruk, Mykola; Oskar Nowicki, M; Aguilar, Estuardo; Aguilar, Laura; Guzik, Brian; Chiocca, Ennio; Lawler, Sean
Abstract: RATIONALE: Dexamethasone is frequently used in symptomatic treatment of glioma patients, although it is known to cause immune suppression. Checkpoint inhibitor immunotherapies have not yet been successful in glioma treatments. Gene-mediated cytotoxic immunotherapy (GMCI) is an immunotherapeutic approach that uses aglatimagene besadenovec with an anti-herpetic prodrug to induce immunogenic tumor cell death and immune cell attraction to the tumor site with potent CD8 T cell activation. GMCI is currently in clinical trials for solid tumors including glioblastoma, where it showed encouraging survival results in a Phase 2 study that did not limit the use of dexamethasone. However, the effects of dexamethasone on its efficacy have not been explored. METHODS: We investigated the effects of dexamethasone on GMCI in vitro using cytotoxicity and T-cell-killing assays in glioblastoma cell lines. The impact of dexamethasone in vivo was assessed in an orthotopic syngeneic murine glioblastoma model. RESULTS: Cyotoxicity assays showed that Dexamethasone has a slight impact on GMCI in vitro . In contrast, we observed a highly significant effect in T-cell-functional assays in which killing was greatly impaired. Immune cell response assays revealed a reduced T-cell proliferation after co-culture with supernatant from dexamethasone or combination treated glioblastoma cells in contrast to GMCI alone. In a murine model, the combination of GMCI and dexamethasone resulted in a significant reduction in median symptom-free survival (29d) in comparison to GMCI alone (39.5d) (P = 0.0184). CONCLUSION: Our data suggest that high doses of dexamethasone may negatively impact the efficacy of immunotherapy for glioma, which may be a consequence of impaired T cell function. These results support the idea that there is a need in identifying possible alternatives to dexamethasone to maximize the effectiveness of immunostimulatory therapies such as GMCI.